2022
DOI: 10.1155/2022/7884401
|View full text |Cite
|
Sign up to set email alerts
|

Rotablation in Patients with Advanced Renal Insufficiency through End-Stage Renal Disease: Short- and Intermediate-Term Results

Abstract: Objective. Patients with advanced renal insufficiency are at high risk of coronary artery disease (CAD) and complex lesions. Treating complex calcified lesion with rotational atherectomy (RA) in these patients might be associated with higher risks and poorer outcomes. This study was set to evaluate features and outcomes of RA in these patients. Method. Consecutive patients who received coronary RA from April 2010 to April 2018 were queried from the Cath Lab database. The procedural details, angiography, and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Differences in categorical data were compared using the Chi-square test and differences in continuous variables were measured by the unpaired Student’s t -test. As our previous studies found that age, renal function (in serum creatinine), multivessel disease (tripe vessel disease plus left main), acute coronary syndrome (ACS), ischemic cardiomyopathy (or cardiogenic shock) and the use of mechanical circulatory support were significant predictors for MACEs in our population ( 15 17 ), and these variables were also predictors of multivariate analyzes in various rotablation registries in European countries ( 13 ), UK ( 32 ), Germany ( 33 ), Poland ( 34 ), Italy ( 35 ), and Japan ( 12 , 36 ). A propensity score-matched analysis was performed to select controls with matched baseline factors to assess the outcomes of RA for CTO lesions as compared with RA for non-CTO lesions, using a matching tolerance of 0.0001.…”
Section: Methodsmentioning
confidence: 57%
See 2 more Smart Citations
“…Differences in categorical data were compared using the Chi-square test and differences in continuous variables were measured by the unpaired Student’s t -test. As our previous studies found that age, renal function (in serum creatinine), multivessel disease (tripe vessel disease plus left main), acute coronary syndrome (ACS), ischemic cardiomyopathy (or cardiogenic shock) and the use of mechanical circulatory support were significant predictors for MACEs in our population ( 15 17 ), and these variables were also predictors of multivariate analyzes in various rotablation registries in European countries ( 13 ), UK ( 32 ), Germany ( 33 ), Poland ( 34 ), Italy ( 35 ), and Japan ( 12 , 36 ). A propensity score-matched analysis was performed to select controls with matched baseline factors to assess the outcomes of RA for CTO lesions as compared with RA for non-CTO lesions, using a matching tolerance of 0.0001.…”
Section: Methodsmentioning
confidence: 57%
“…However, their use of RA for CTO involved patients who were significantly younger and had much more stable angina, which would otherwise confound the outcome assessment. In our previous publications, we have identified age, diabetes, renal insufficiency, ACS, shock, ischemic cardiomyopathy, MVD, and residual Syntax score as prognostic factors of short and intermediate outcomes ( 15 17 ). These variables were also independent predictors for major cardiovascular events in previous publication ( 12 , 23 , 33 – 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation